EFFECT OF CHINESE MEDICAL HERBS- BURN LINIMENT ON DEEP SECOND DEGREE BURN IN RATS - Wang, Xiong; Zhao, Si Qian; Zhao, Li Chao; Guo, Hao; Peng, Wei Si; Wu, Hu Jin (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Burn Liniment (BL) is a popular traditional Chinese medicine formula consisting five herbal medicines (Flos Lonicerae, Rhizoma Polygoni Cuspidati, Pericarpium Granati,Terminalia chebula Retz. and Galla Chinensis), that has been used in China for centuries to cure burn. This study investigated the healing effect of BL on deep second degree burn wounds in rats. Materials and methods: The animals were divided into four groups including control group, model group,1% silver sulfadiazine (SSD) group and BL group. On days 0,3,7,14 and 21,animal weight, wound area as well as histo-pathological observations of the skin were evaluated in different groups. Serum anti-intercellular adhesion molecule 1(ICAM-1), IL-10 levels and myeloperoxidase (MPO) activity were measured on the 21st day. HPLC chromatography of BL was prepared and concentrations of active constituents were determined. Antibacterial test and toxicological test were also performed. Results: The average wound area of BL treatment group was also significantly smaller than model control rats on days 14 and 21. Serum anti-intercellular adhesion molecule 1(ICAM-1) levels and myeloperoxidase (MPO) activity of BL group decreased significantly than in model rats on day 21 while IL-10 level of BL group increased remarkably than in model rats on the 21st day, showing that BL has strong anti-inflammatory activity on burned rats. The histological studies indicated that inflammatory cells disappeared significantly and were replaced by new granulation tissue, and epithelialization progressed quickly and was treated with BL on the 21st day. Meanwhile, HPLC chromatography of BL was prepared and concentration of Chlorogenic acid, Polydatin and Gallic acid from BL were determined. Antibacterial test revealed that the MIC of BL on Staphyloccocus aureus, Pseudomonas aeruginosa and Escherichia coli were 1.56, 6.25 and 1.56 mg•mL-1 respectively. Toxicological test showed that BL does not induce skin irritation or sensitivity signs and has no acute toxicity reaction. Conclusions: Our study revealed that BL could enhance cutaneous burn wound healing effectively. It also showed strong anti-inflammatory and antibacterial activity in rats.